Epidemiological characteristics of patients with Covid-19 suspicion applying to a university hospital: The first eighty days in a pandemic - Durduran, Yasemin; Kandemir, Bahar; Demir, Lutfi Saltuk; Ozdemir, Mehmet; Erayman, Ibrahim; Uyar, Mehmet; Kurt, Esma Kepenek; Kocak, Sedat; Vatansev, Hulya; Yosunkaya, Alper; Zamani, Adil; Kadiyoran, Cengiz; et al. (Annals of Medical Research, 2021)
Aim: The first COVID-19 case in Turkey was detected on March 11, 2020 during the COVID-19 pandemic process. Epidemiologicalstudies are needed to be prepared for other outbreaks and to be effective in the disease management process. Based on this reason,in this study it was aimed to determine the epidemiological characteristics of Covid 19 possible and definite cases who applied tothe university hospital during the pandemic process.Materials and Methods: This retrospective epidemiological study was carried out by analyzing the data of Covid 19 possible anddefinite cases, who applied to the university hospital operating as a pandemic hospital between 11 March / 01 June 2020. The datawere summarized with descriptive statistics, tables and graphs.Results: Of the 1,383 patients, who applied with the suspicion of COVID-19, 55.5% were men and 84.5% were adults. The medianage of children is 4.0 (1.5-10) years old; adults were 52.0 (36.0-67.0) years old. The median time between the outset of complaintsand the date of admission to the hospital was 2 (1-3) days. 87.4% of adults and 87.9% of children had symptoms that supportedCOVID-19 infection. Among cases 7.8% were health care workers. The median age of the fatal cases was 71 (64-82) years old, 79.5%were male, 77.7% were retired. The most common comorbide diseases in these cases were hypertension (28.2%) and malignancy(28.2%). The case fatality rate was found as 2.8% in all patients and 48.4% in patients hospitalized in the intensive care unit.Conclusions: As a result, Covid-19 affects all age groups. Hypertension and malignancy were the most common additional diseasesin fatal cases. The risk of illness is higher in healthcare workers who have direct contact with the patients. According to ourobservations, preventive measures, rapid diagnosis and supportive treatment are valuable.
Keywords: Covid-19; epidemiological characteristics; pandemic process; university hospital